Anxiety, depressive symptoms, and distress over the course of the war in Ukraine in three federal states in Germany - Massag, Janka; Diexer, Sophie; Klee, Bianca; Costa, Daniela; Gottschick, Cornelia; Broda, Anja; Purschke, Oliver; Opel, Nils; Binder, Mascha; Sedding, Daniel; Frese, Thomas; Girndt, Matthias; et al. (Frontiers in Psychiatry, 2023)
Introduction: The Russian invasion of Ukraine and the resulting consequences are in the center of political discussions, media, and likely individual thinking of the population in Germany. Yet, the impact of this prolonged exposure on mental health is not known hitherto. Methods: Using the population based cohort study DigiHero from three federal states (Saxony-Anhalt, Saxony, and Bavaria), we assessed anxiety levels (GAD-7), depressive symptoms (PHQ-9), and distress (modified PDI) in the first weeks of war and six months later. Results: Of those 19,432, who responded in the first weeks of war, 13,934 (71∙1%) responded also six months later. While anxiety and emotional distress decreased during the six months, their average scores were still elevated, and a substantial fraction of respondents displayed clinically relevant sequelae. Persons from low-income households were especially affected, specifically by fears related to the personal financial situation. Those who reacted with a particularly strong fear in the beginning of war were more likely to have persistent clinically relevant symptoms of depression and anxiety also six months later. Discussion: The Russian invasion of Ukraine is accompanied by continuing impairment of mental health in the German population. Fears surrounding the personal financial situation are a strong determinant.